Fatores preditores para mortalidade por sepse em uma unidade de terapia intensiva pediátrica - Sales, Nádia de Sousa (2018)
Sepsis is a syndrome caused by the systemic inflammatory response of infectious origin, being complex and characterized by different manifestations that can lead to the failure of one or more organs and until death. The present study aims to identify predictive factors for sepsis mortality in pediatric patients hospitalized in an Intensive Care Unit (ICU). The sample consisted of all hospital records of patients admitted from April 2016 to April 2018 with a confirmed diagnosis of sepsis, arising from pediatric emergency, pediatric clinic, surgery center or referred by other hospitals and who remained in the sector for more of 24 hours. Neonatal, pediatric and in -hospital variables were related to the outcome using multivariate logistic regression, using Soltware R. Form included 209 children, of whom 11% died, most of them younger than 1 year and female. The prematurity variable was related to the worst outcome, but at the end of the model adjustment and exclusion of the non-significant or biased variables, there remained as significant, septic shock (exp {1,257} = 3.51), IMP II below 15%, exp {1,712} = 5.54), hospitalization up to the 28th day of birth (exp {1,540} = 4.66), and comorbidities (exp {1,129} = 3.09). Measures to reduce prematurity and management during the hospitalization of newborns, attention to patients with multiple diseases and update of established sepsis protocols are measures that would reduce the negative impact of these variables.